1980
DOI: 10.1161/01.cir.62.6.1297
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic study of the paradoxical arterial pulse in chronic obstructive lung disease.

Abstract: In nine subjects with chronic obstructive pulmonary disease (COPD) and pulsus paradoxus, M-mode echocardiograms showed inspiratory augmentation of right ventricular dimensions and inspiratory decrease of left ventricular diastolic dimensions. In five subjects in whom the echocardiographic transistor was in the subxiphoid position, mean right ventricular dimensions increased during inspiration from 1.4 +/- 0.20 to 2.96 +/- 0.38 cm (p < 0.01). With inspiration, mean left ventricular diastolic dimensions decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…SETTLE et al [30], studying stable COPD patients, observed an increase in RV dimension during inspiration associated with a reduction in LV dimensions. Similarly, JARDIN and co-workers [31], studying mild acute exacerbation of COPD, found increased RV dimensions when compared to a control group.…”
Section: Effects Of Peepi On Cardiopulmonary Interaction During Weaningmentioning
confidence: 98%
“…SETTLE et al [30], studying stable COPD patients, observed an increase in RV dimension during inspiration associated with a reduction in LV dimensions. Similarly, JARDIN and co-workers [31], studying mild acute exacerbation of COPD, found increased RV dimensions when compared to a control group.…”
Section: Effects Of Peepi On Cardiopulmonary Interaction During Weaningmentioning
confidence: 98%
“…In addition, right ventricular afterload should increase during inspiration (breathing at high lung volume). During acute exacerbation of COPD, where the right ventricle can already be enlarged, combination of increased right ventricular preload and increased right ventricular afterload during inspiration should result in a marked parallel biventricular interdependence phenomenon, as demonstrated by SETTLE et al [32] in an electrocardiographic study. This can contribute to the development of pulsus paradoxus during acute exacerbation of COPD.…”
Section: Pulsus Paradoxus In Acute Asthmamentioning
confidence: 88%
“…The reduction in left ventricular preload during inspiration, which is thus the most plausible explanation, could be due: either to 1) series ventricular interaction (see above), making the right and left ventricles 180u out of phase; 2) reduction in left ventricular diastolic time related to the increased heart rate accompanying inspiration; or 3) the parallel ventricular interdependence phenomenon. However, it is unlikely that the latter mechanism is significant in the absence of pericardial constraint or of right ventricle overdistension during normal inspiration [32]. Another possible mechanism could be an inspiratory pulmonary venous blood pooling, related to the fact that pulmonary vessels are supposed to be more compliant than the left ventricle [25,33].…”
Section: Mechanisms Of Pulsus Paradoxusmentioning
confidence: 99%
“…Moreover, it was previously demonstrated via magnetic resonance angiography that the pulmonic vein area of patients with COPD is smaller, suggesting underfilling of their LA [20]. Proposed mechanisms for decreased left side filling in patients with COPD include an altered intrathoracic pressure, increased pulmonary veins resistance, compression of alveolar vessels [20], increased heart rate [19], systemic vasodilation [21], and bulging of the septum due to right heart dilatation [22,23]. Investigating the etiologies of small LA size on CT, Cassagnes et al [6] reported that patients with emphysema had an inverse correlation between LA volume and the severity of emphysema.…”
Section: Discussionmentioning
confidence: 99%